PERAN INFORMASI AKUNTANSI DALAM MENINGKATKAN PERTUMBUHAN KINERJA USAHA MIKRO, KECIL, DAN MENENGAH - Bulan Nettiary (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
The purpose of writing is to find out and analyze the role of accounting information in increasing the growth of MSME performance in cafe in Palembang. The data analyzed are the results of the interview method with 5 informants namely the owner of UMKM in the culinary field in the form of a restaurant. Data were analyzed using qualitative descriptive analysis. The results showed that accounting information has a role in increasing the growth of MSME performance. This result can be seen that some MSMEs have used accounting information in running their business. From a number of MSMEs studied also showed that they took business actions and decisions using accounting information in accordance with accounting theory, only they were unaware of it. This is because the owner does not have an accounting education background. The improvement in MSME performance growth can be seen from the increase in sales, cost reduction, and the addition of assets to MSMEs that have used accounting information well.